Dear Palestine: a social history of the 1948 war - Hazkani, Shay ca. 20./21. Jh. (Stanford studies in Middle Eastern and Islamic societies and cultures, 2021)
"This book recasts the 1948 war in Palestine through a socio-cultural history of the conflict's ordinary actors and its transnational reverberations. It draws on untapped personal letters of Jews and Arabs from the war, most of whom fought in the ranks of the Israel Defense Forces (IDF), or the Arab League's volunteer army, known as the Arab Liberation Army (ALA). The examination of these letters challenges the war accounts of politicians and generals, whose words continue to shape histories of the Israeli-Palestinian conflict. These conventional accounts of the war in Palestine suggest clearly drawn battle lines, and an intractable present and future. "Dear Palestine," meanwhile, shows that the stories ordinary people told themselves about the war were far more diverse and complex than the nationalist fervor and unquestioning loyalty to the cause usually imputed to them. Still, understanding what ordinary people said to one another in private letters is impossible without also taking into account the efforts of elites to inculcate certain ideologies in them. To do so, this book also examines battle orders, pamphlets, army magazines, and radio broadcasts used to mobilize young men and women, and to educate and indoctrinate them in their respective armies. Reading indoctrination materials alongside soldiers' letters reveals important and enduring fissures in the ideological edifices of Middle East nationalisms even at the moment when, by most accounts, these conceptions of nationalism crystallized. It also shows normal, everyday people's fear, bravery, failure, arrogance, cruelty, lies, and exaggerations, which are so often excluded from history"--